THE CONCEPT OF BILINGUAL EDUCATION, AS A MEASURE OF THE EDUCATIONAL SYSTEM OF UKRAINE WITH THE EU STANDARDS - Івашкіна I.; Шевченко A. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
This article discusses the concept of bilingual education as a means of harmonizing the educational system of Ukraine with EU standards. The urgency of this topic is that due to its polyethnicity, Ukrainian society needs the formation of a polycamous personality that can adapt to professional reforms in a globalized world. Consideration of this topic is also important because of the ethnic and social tensions that are present in some EU countries and are due to linguistic differentiation historically formed in the same geographic area. The purpose of this article is to study the concept of bilingual education and its impact on personality. In the course of writing this work, the method of analysis was used to compare the curricula of bilingual education of higher education institutions of the EU countries. The article examines the experience of bilingual education in the EU countries, Also, three types of bilingual education concepts in the EU were derived by the authors of this article. The article suggests ways to implement the bilingual system of education in the system of higher education of Ukraine